A review of technical advances of recent palm bio-waste conversion to activated carbon for energy storage - Ayinla, R.T. (Elsevier Ltd, 2019)
Recently, the conversion of palm waste to activated carbon for various applications has attracted significant attention from researchers. Over the years, abundant palm wastes have been generated due to active palm milling in various part of the world. These environmentally challenging wastes have been converted to valuable and economical materials for gas adsorption and water treatment but rarely for energy storage application. The lignocellulose composition of palm wastes has made it a favorable candidate for starting material of activated carbon for supercapacitor application. In this review, the pretreatment condition, factors to consider for choosing starting material, activation techniques, and activation parameters such as activation temperature, activation time, activation agent and impregnation ratio are analyzed. The advantages of the synergistic effect of the lignocellulose composition of different palm wastes for energy storage device is discussed. The major drawbacks in the conventional Barrett-Joiner-Halenda (BJH) porosity characterization technique are addressed and the novel Non-localized Density Functional Theory characterization technique is suggested. Conclusively, future prospects in the activation of palm bio-wastes for supercapacitor application are highlighted. Â© 2019 Elsevier Ltd